Implementation of Indigenous Peoples Traditions based on Tourism Development in Kampung Naga - Muhammad Fakhri Jamaluddin (Jurnal Hospitality dan Pariwisata, 2021)
Tasikmalaya Regency is one of the areas in West Java Province which has a type of cultural tourism as its attraction. The type of potential cultural tourism in this regency is located in the Traditional Dragon Village Area, precisely in Neglasari Village, Salawu District. Kampung Naga is an area where the people still hold the beliefs or customs of their ancestors. The large number of tourists visiting Kampung Naga will have a positive or negative impact on this tradition. The purpose of this study is to identify the impact of tourism development on the life of the indigenous people of Kampung Naga, especially in implementing its traditions. The presence of tourists can affect the traditional life and culture of the local community, therefore it is necessary to have research on changes in the implementation of traditions (customs and customs) after the presence of tourists in the Kampung Naga area. The analytical method used is descriptive qualitative data analysis using the interactive model of Miles and Huberman. Based on this analysis, there are several changes in the implementation of the tradition as an impact felt by the local community after the development of tourism. The results of this identification are expected to be considered in tourism planning and development related to tourism policies and the ecosystem therein. Because by implementing a good and appropriate policy, the potential of the existing tourism area can run optimally by minimizing the negative impact on humans.